Future strategies to improve short-and long-term outcomes of renal transplantation in dogs - Rocha, Guilherme Lages Savassi; Crivellenti, Leandro Zuccolotto; Braz, Larissa Ayane Do Nascimento [UNESP]; Maia, Suellen Rodrigues [UNESP]; Faria, Luciano Alves; Alvarenga, Alef Winter Oliveira; Fernandes, André Luiz Sampaio (FapUNIFESP (SciELO), 2021)
Transplants for cats with naturally occurring renal disease have been introduced into clinical practice, but canine renal transplantation represents a greater challenge because of the lack of a balanced immunosuppressive protocol, difficulty in selecting compatible canine kidney donors, and absence of transplantation monitoring protocols. This and other important factors will be discussed in this review to help improve short-and long-term outcomes for renal transplantation in dogs.
Estratégias futuras para melhorar os resultados de transplante renal em cães a curto e longo prazo
Keywords: Immunosupression; Renal replacement therapy; Veterinary medicine